The complete sequence of a human genome - Nurk, Sergey; Koren, Sergey; Rhie, Arang; Rautiainen, Mikko; Bzikadze, Andrey V; Mikheenko, Alla; Vollger, Mitchell R; Altemose, Nicolas; Uralsky, Lev; Gershman, Ariel; Aganezov, Sergey; Hoyt, Savannah J; et al. (Science (American Association for the Advancement of Science), 2022)
Since its initial release in 2000, the human reference genome has covered only the euchromatic fraction of the genome, leaving important heterochromatic regions unfinished. Addressing the remaining 8% of the genome, the Telomere-to-Telomere (T2T) Consortium presents a complete 3.055 billion-base pair sequence of a human genome, T2T-CHM13, that includes gapless assemblies for all chromosomes except Y, corrects errors in the prior references, and introduces nearly 200 million base pairs of sequence containing 1956 gene predictions, 99 of which are predicted to be protein coding. The completed regions include all centromeric satellite arrays, recent segmental duplications, and the short arms of all five acrocentric chromosomes, unlocking these complex regions of the genome to variational and functional studies.